Creative Strategy of Kokoru Media (Colour Corrugated Paper) in Improving Folding Ability and Recognizing Colors in Group B - Ni Nyoman Novita Angginingsih; Nice Maylani Asril; Gede Wira Bayu (Universitas Pendidikan Ganesha, 2025)
This research is motivated by the low ability to fold and recognize colors in group B children in kindergarten, which shows the need for more interesting learning media innovations that are in accordance with the stage of early childhood development. This research aims to develop and evaluate the effectiveness of kokoru (colour corrugated paper) media in improving the ability to fold and recognize colors in children. The subjects of this study were 26 children of group B of kindergarten which were divided into two groups, namely the experimental group and the control group. This study uses a development research method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model and a quasi-experimental approach with a post-test only control group design. Data collection techniques are carried out through observation, performance task assessment, and documentation during the learning process. The data obtained were then analyzed using descriptive statistical analysis and the Mann–Whitney U comparative test to determine the difference in results between the two groups. The results showed that the use of kokoru media was effective in improving folding and color recognition skills in group B children, with the effectiveness of folding ability reaching 89% and color recognition reaching 92%. These findings show that kokoru media can be an innovative and interesting alternative learning media in supporting early childhood fine motor and cognitive development.